Review paper Menopause and skin aging - Wojnowska, Dorota; Juszkiewicz-Borowiec, Maria; Chodorowska, Grażyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
The skin is one of the organs, which is influenced by sex steroids, especially estrogen and testosterone. Estrogen receptors are found in the whole skin, with the density of receptors being highest on the face, pubic region, genitalia and lower limbs. Pregnancy, menstruation and menopause modulate the skin appearance and properties, especially during menopause the skin undergoes profound changes. Postmenopausal women often complain of dry, atrophic, slack skin with increased wrinkling. The altered biomechanical properties of the skin in climacteric women cause certain disorders, such as atrophic vulvovaginitis, dysaesthetic vulvodynia, vulval lichen sclerosus, facial hirsutism, frontal fibrosing alopecia and recurrent menopausal flushing. Although skin aging is certainly no indication for the hormone replacement therapy the beneficial effect of estrogen supplementation on the skin appearance is a positive side aspect of such treatment.